Impact of long-term transmural plastic stents on recurrence after endoscopic treatment of walled-off pancreatic necrosis - de Jong, David M; Stassen, Pauline M. C.; Schoots, Ivo G.; Verdonk, Robert C.; Bruno, Marco J.; Voermans, Rogier P.; de Jonge, Pieter Jan F. (Endoscopy, 2024)
Background Endoscopic transmural drainage (ETD) using double-pigtail stents (DPSs) is a well-established treatment for walled-off pancreatic necrosis (WON). This study aimed to compare outcomes in patients undergoing ETD with DPSs left indwelling versus those where stents were removed or migrated.Methods This retrospective multicenter cohort study included patients with WON who underwent ETD using DPSs between July 2001 and December 2019. The primary outcome was recurrence of a pancreatic fluid collection (PFC). Secondary outcomes were long-term complications and recurrence-associated factors. Competing risk regression analysis considered DPS removal or migration as time-varying covariates.Results Among 320 patients (median age 58; 36% women), DPSs were removed in 153 (47.8%), migrated spontaneously in 27 (8.4%), and remained indwelling in 140 (43.8%). PFC recurrence was observed in 57 patients (17.8%): after removal (n = 39; 25.5%); after migration (n = 4; 14.8%); in patients with indwelling DPSs (n = 14; 10.0%). In 25 patients (7.8%), drainage of recurrent PFC was indicated. Risk factors for recurrence were DPS removal or migration (hazard ratio [HR] 3.45, 95%CI 1.37–8.70) and presence of a disconnected pancreatic duct (HR 5.08, 95%CI 1.84–14.0).Conclusions Among patients who undergo ETD of WON, leaving DPSs in situ seems to lower the risk of recurrent fluid collections, without any long-term DPS-related complications. These results suggest that DPSs should not be routinely removed and can be safely left indwelling indefinitely.